Analysis of Multipurpose Container-Passenger Vessel (MCPV) with Detachable Superstructure to Improve Inter-Island Access in Talaud Island - arif Riansyah; M Rizki Aliya; Gizza Gaeta Nahumariri Gaeta Nahumariri (Puslitbang Transportasi Antarmoda-Kementerian Perhubungan Republik Indonesia, 2019)
In 2012, Indonesia developed a National Logistic System (SISLOGAS) framework perceived in Peraturan Presiden (Perpres) No. 26 of 2012, in accordance with the Master Plan of Acceleration and Expansion of Indonesia’s Economic Development (MP3EI). One of the plans consisted in SISLOGAS was the improvement of inter-island transportation networks through Short Sea Shipping (SSS) by providing appropriate vessel which had been applied on Kontainer Masuk Desa program and was previously tested in the Talaud Island as the outermost area of Indonesia. Aside from being located in the outermost Indonesia’s territory, Talaud Island is one of the marine tourism destinations in North Sulawesi, hence this island needs an inter-island crossing vessel when high demand comes (holiday season). However, due to geographical conditions of Talaud Island which only has an average maximum depth of 6m and the underwater volcano Kawio Barat-Mahangetang which emerges from 5.4-8 m above sea level, could be a problematic for larger ships to sail thus small ships for transportation are required. Seeing the needs equally the existing potential, the making of a Multipurpose Container - Passenger Vessel (MCPV) with Detachable Superstructure could be a solution. Alongside specification of length: 20,85 m, breadth: 7 m, draft: 1,4 m, height 2 m and displacement: 181,32 tons, MCPV could carry containers reaching a weight of 77,28 tons and sail in shallow water by using an engine made by YANMAR which could produce 10 knots speed, besides, MCPV is also equipped with detachable container that could be replaced as reauested both for transportation of goods and people. By the existence of MCPV, it is expected to be able to improve inter-island transportation networks.